Identification of Mothballed and Retired Units of Reliability-Based Steam Power Generation Systems - M Sabri (Jurnal POLIMESIN, 2022)
A steam power generation system is a power generation system that uses steam power. The generating system itself has two types of unit statuses, namely active and inactive, which in this case are subdivided into Mothballed and Retired Unit statuses. The status of the unit provides a statement or decides whether the generating system is still suitable for use or has to be replaced (inactive). Determination of the status of the unit in the steam power generation system is carried out by calculating the work reliability of the generating unit. This is done to get the maximum decision. If you set the unit status incorrectly, the production costs incurred will be greater and not proportional to the number of products produced. This study focuses on two power generation units that have been used for a long time and experienced a decrease in performance. Therefore, identification of the status of the Mothballed and Retired Units of the steam power generation system was carried out by using a reliability test so as to produce a decision in determining the status of a more reliable unit. The method used to determine the status of the unit is to use the Reliability Block Diagram (RBD) and the Generating Availability Data System (GADS), the results of which state that unit one is in Mothballed status, which means the unit is no longer active but can still be used or reactivated within a period of several months. with a reliability level of 4.92% if it operates for 800 hours or a month. Meanwhile, unit two is declared to have the status of Retired Unit or can no longer be used again.